Studi Pemikiran Pendidikan Islam Tokoh Pendidikan Indonesia “Buya Hamka” - Ilham Kurniawan; Lukmanul Hakim; Abdullah .; Mulyanto Abdul Khoir (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This paper examines Buya Hamka’s Islamic educational thought as that of one of Indonesia’s prominent intellectuals and educators who made significant contributions to the development of integrative Islamic education. This study is grounded in the reality of the national education system, which frequently experiences curriculum changes without being accompanied by adequate reinforcement of spiritual and moral values. The study aims to explore Buya Hamka’s biography, his conception of Islamic education, and the relevance of his ideas to contemporary educational contexts. Employing a library research approach, this study analyzes Buya Hamka’s works alongside other relevant scholarly literature. The findings reveal that Buya Hamka perceives education as a process of holistic development encompassing both physical and spiritual dimensions rooted in human fitrah, with the objective of forming individuals who are faithful, morally upright, and intellectually competent. According to Buya Hamka, education should integrate religious knowledge and general sciences in a balanced manner in order to cultivate individuals who attain well-being in both worldly life and the hereafter. Buya Hamka’s educational thought remains highly relevant in responding to the challenges of modern education, which tends to be secular and materialistic, and may serve as an important reference for the development of holistic and character-based Islamic education.